Jana Szymczyka rozumienie aksjologicznego wymiaru polskiej socjologii - Jabłoński, Arkadiusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The article concerns the issue of Jan Szymczyk’s understanding of Polish sociology as rooted in universal humanistic values. The aim of the article is to show Szymczyk’s contribution to understanding the heritage of Polish sociology as related to a specific system of values, which determines the way of identifying real sociological problems and searching for the best solutions to them. In Szymczyk’s writings, reference to Polish sociology takes the form of a deliberate procedure of deepening the tradition of sociological thinking and embedding it in the historical conditions of life of a specific community. Nonetheless, the Lublin sociologist did not believe that social order should be discussed within the framework of national sociologies, but claimed that a universal scientific language requires embedding in the system of values appropriate for a given national community.